Disease characteristics and progression in patients with late-infantile neuronal ceroid lipofuscinosis type 2 (CLN2) disease: an observational cohort study. (August 2018) - Nickel, Miriam; Simonati, Alessandro; Jacoby, David; Lezius, Susanne; Kilian, Dirk; Van de Graaf, Benjamin; Pagovich, Odelya E; Kosofsky, Barry; Yohay, Kaleb; Downs, Matthew; Slasor, Peter; Ajayi, Temitayo; et al.
Summary: Background: Late-infantile neuronal ceroid lipofuscinosis type 2 (CLN2) disease, characterised by rapid psychomotor decline and epilepsy, is caused by deficiency of the lysosomal enzyme tripeptidyl peptidase 1. We aimed to analyse the characteristics and rate of progression of CLN2 disease in an international cohort of patients. Methods: We did an observational cohort study using data from two independent, international datasets of patients with untreated genotypically confirmed CLN2 disease: the DEM-CHILD dataset (n=74) and the Weill Cornell Medical College (WCMC) dataset (n=66). Both datasets included quantitative rating assessments with disease-specific clinical domain scores, and disease course was measured longitudinally in 67 patients in the DEM-CHILD cohort. We analysed these data to determine age of disease onset and diagnosis, as well as disease progression—measured by the rate of decline in motor and language summary scores (on a scale of 0–6 points)—and time from first symptom to death. Findings: In the combined DEM-CHILD and WCMC dataset, median age was 35·0 months (IQR 24·0–38·5) at first clinical symptom, 37·0 months (IQR 35·0 −42·0) at first seizure, and 54·0 months (IQR 47·5–60·0) at diagnosis. Of 74 patients in the DEM-CHILD dataset, the most common first symptoms of disease were seizures (52 [70%]), language difficulty (42 [57%]), motor difficulty (30 [41%]), behavioural abnormality (12 [16%]), and dementia (seven [9%]). Among the 41 patients in the DEM-CHILD dataset for whom longitudinal assessments spanning the entire disease course were available, a rapid annual decline of 1·81 score units (95% CI 1·50–2·12) was seen in motor–language summary scores from normal (score of 6) to no function (score of 0), which occurred over approximately 30 months. Among 53 patients in the DEM-CHILD cohort with available data, the median time between onset of first disease symptom and death was 7·8 years (SE 0·9) years. Interpretation: In view of its natural history, late-infantile CLN2 disease should be considered in young children with delayed language acquisition and new onset of seizures. CLN2 disease has a largely predictable time course with regard to the loss of language and motor function, and these data might serve as historical controls for the assessment of current and future therapies. Funding: EU Seventh Framework Program, German Ministry of Education and Research, EU Horizon2020 Program, National Institutes of Health, Nathan's Battle Foundation, Cures Within Reach Foundation, Noah's Hope Foundation, Hope4Bridget Foundation.